2006
DOI: 10.1088/0960-1317/16/4/021
|View full text |Cite
|
Sign up to set email alerts
|

End-coupled optical waveguide MEMS devices in the indium phosphide material system

Abstract: We demonstrate electrostatically actuated end-coupled optical waveguide devices in the indium phosphide (InP) material system. The design of a suitable layer structure and fabrication process for actuated InP-based waveguide micro-electro-mechanical systems (MEMS) is reviewed. Critical issues for optical design, such as coupling losses, are discussed and their effect on device performance is evaluated. Several end-coupled waveguide devices are demonstrated, including 1 × 2 optical switches and resonant sensors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
37
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 33 publications
(65 reference statements)
0
37
0
Order By: Relevance
“…The angular displacement of mirror can be equally converted to a lateral misalignment x and angular offset 2 between the two fibers, where x can be approximately represented as d ϫ 2. Accordingly, the insertion loss IL 2 can be calculated theoretically using the formula derive from [12][13][14] …”
Section: Optical Designmentioning
confidence: 99%
“…The angular displacement of mirror can be equally converted to a lateral misalignment x and angular offset 2 between the two fibers, where x can be approximately represented as d ϫ 2. Accordingly, the insertion loss IL 2 can be calculated theoretically using the formula derive from [12][13][14] …”
Section: Optical Designmentioning
confidence: 99%
“…Pérez-Murano, Á. San Paulo and O. Gottlieb, " Top-down silicon microcantilever with coupled bottom-up silicon nanowire for enhanced mass resolution," Nanotechnology 26 (14), 145502 (2015).…”
mentioning
confidence: 99%
“…The mechanical vibrations are imprinted on the optical signal by their perturbation of the mode coupling over the gap between the two SWG, [14]. The transmission can be described by,…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1,5 Recently, it was shown that motion of micron-scale devices can be monitored through changes in end-to-end alignment of optical waveguides. [9][10][11] In this letter, we propose an integrated and near-field optical motion detection technique that exploits near-field optical evanescent-wave coupling. We demonstrate that the technique works efficiently for nanoscale mechanical resonators, with greater sensitivity than conventional optical techniques.…”
mentioning
confidence: 99%